Therapeutic pathomorphism of malignancies: Clinical and morphological criteria. Classifications. Prognostic value of therapeutic pathomorphism in breast cancer and other tumors - A. A. Lisayeva; Ya. V. Vishnevskaya; E. M. Roshchin; D. V. Komov; I. V. Kolyadina (Опухоли женской репродуктивной системы)
Pathomorphism is one of the most important prognostic factors for breast cancer . The paper gives the notion of pathomorphism an d its types and the most commonly used classifications of tumor pathomorphological changes. It also considers the long-term results of neoadjuvant treatment in relation to pathomorphism.